Seasonal affective disorder and seasonal changes in weight and sleep duration are inversely associated with plasma adiponectin levels. (March 2020) - Akram, Faisal; Gragnoli, Claudia; Raheja, Uttam K.; Snitker, Soren; Lowry, Christopher A.; Stearns-Yoder, Kelly A.; Hoisington, Andrew J.; Brenner, Lisa A.; Saunders, Erika; Stiller, John W.; Ryan, Kathleen A.; Rohan, Kelly J.; et al.
Abstract: Overlapping pathways between mood and metabolic regulation have increasingly been reported. Although impaired regulation of adiponectin, a major metabolism-regulating hormone, has been implicated in major depressive disorder, its role in seasonal changes in mood and seasonal affective disorder-winter type (SAD), a disorder characterized by onset of mood impairment and metabolic dysregulation (e.g., carbohydrate craving and weight gain) in fall/winter and spontaneous alleviation in spring/summer, has not been previously studied. We studied a convenience sample of 636 Old Order Amish (mean (± SD), 53.6 (±14.8) years; 50.1% males), a population with self-imposed restriction on network electric light at home, and low prevalence of total SAD (t-SAD = syndromal + subsyndromal). We calculated the global seasonality score (GSS), estimated SAD and subsyndromal-SAD after obtaining Seasonal Pattern Assessment Questionnaires (SPAQs), and measured overnight fasting plasma adiponectin levels. We then tested associations between plasma adiponectin levels and GSS, t-SAD, winter-summer difference in self-reported sleep duration, and self-reported seasonal weight change, by using analysis of co-variance (ANCOVA) and linear regression analysis after adjusting for age, gender, and BMI. Participants with t-SAD ( N = 14; 2.2%) had significantly lower plasma adiponectin levels (mean ± SEM, 8.76 ± 1.56 μg/mL) than those without t-SAD (mean ± SEM, 11.93 ± 0.22 μg/mL) ( p = 0.035). In addition, there was significant negative association between adiponectin levels and winter-summer difference in self-reported sleep duration ( p = 0.025) and between adiponectin levels and self-reported seasonal change in weight ( p = 0.006). There was no significant association between GSS and adiponectin levels ( p = 0.88). To our knowledge, this is the first study testing the association of SAD with adiponectin levels. Replication and extension of our findings longitudinally and, then, interventionally, may implicate low adiponectin as a novel target for therapeutic intervention in SAD.